IMPLIKASI DOMINASI STRUKTURAL TERHADAP PERLINDUNGAN HAK ASASI PEREMPUAN DALAM KESETARAAN KESEMPATAN KERJA DI INDONESIA - Nola Listi Fitriani; Amanda Putri; Naura Putri Ramadhania; Asep Suherman (CV. Denasya Smart Publisher, 2025)
The phenomenon of structural domination in Indonesian society contributes significantly to the gender gap that still persists today. Structural domination refers to a social system that systematically discriminates against women, both in access to employment. This study aims to answer the questions, namely: What are the legal implications of structural domination on gender gaps in employment in Indonesia and What is the urgency of legal protection reform to create fairer and more gender-equal legal policies in Indonesia, this study uses normative research methods. The results of this study indicate that structural domination that benefits men and discrimination against women, especially in terms of wages, job opportunities, promotions, and legal protection, is still a major challenge in the Indonesian employment sector. Fair employment opportunity reform also requires changes to address structural barriers to women's access to strategic positions, including competency-based recruitment systems.